Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve [tex]\( \tan(x)(\tan(x) + 1) = 0 \)[/tex]:

A. [tex]\( x = \pm n\pi, x = \frac{\pi}{4} \pm n\pi \)[/tex]

B. [tex]\( x = \frac{\pi}{3} \pm 2\pi n, x = \frac{3\pi}{4} \pm 2\pi n \)[/tex]

C. [tex]\( x = \pm \pi n, x = \frac{\pi}{2} \pm 2\pi n \)[/tex]

D. [tex]\( x = \pm \pi n, x = \frac{3\pi}{4} \pm \pi n \)[/tex]


Sagot :

To solve the equation [tex]\(\tan(x)(\tan(x) + 1) = 0\)[/tex], we look for the values of [tex]\(x\)[/tex] that satisfy the equation.

First, let's break the original equation into its factors:
[tex]\[ \tan(x) \cdot (\tan(x) + 1) = 0 \][/tex]

For this product to be zero, at least one of the factors must be zero. This gives us two separate equations to solve:
1. [tex]\(\tan(x) = 0\)[/tex]
2. [tex]\(\tan(x) + 1 = 0\)[/tex]

### Solving [tex]\(\tan(x) = 0\)[/tex]

The tangent function [tex]\(\tan(x)\)[/tex] is zero at integer multiples of [tex]\(\pi\)[/tex]:
[tex]\[ x = n\pi \quad \text{for any integer } n. \][/tex]

### Solving [tex]\(\tan(x) + 1 = 0\)[/tex]

Rewriting the equation, we get:
[tex]\[ \tan(x) = -1 \][/tex]

The tangent function [tex]\(\tan(x)\)[/tex] equals [tex]\(-1\)[/tex] at angles where [tex]\(x\)[/tex] is an odd multiple of [tex]\(\frac{\pi}{4}\)[/tex]. Therefore:
[tex]\[ x = \frac{3\pi}{4} + n\pi \quad \text{for any integer } n. \][/tex]

Combining both solutions, we obtain:
[tex]\[ x = n\pi \quad \text{and} \quad x = \frac{3\pi}{4} + n\pi \quad \text{for any integer } n. \][/tex]

Now we match these combined solutions with the given answer choices:
[tex]\[ \text{A. } x= \pm n\pi, \quad x=\frac{\pi}{4} \pm n\pi \][/tex]
[tex]\[ \text{B. } x=\frac{\pi}{3} \pm 2 \pi n, \quad x=\frac{3 \pi}{4} \pm 2 \pi n \][/tex]
[tex]\[ \text{C. } x=\pm \pi n, \quad x=\frac{\pi}{2} \pm 2 \pi n \][/tex]
[tex]\[ \text{D. } x= \pm \pi n, \quad x=\frac{3 \pi}{4} \pm \pi n \][/tex]

The combined solutions [tex]\(x = n\pi \quad \text{and} \quad x = \frac{3\pi}{4} + n\pi\)[/tex] correspond to choice D:
[tex]\[ \text{D. } x= \pm \pi n, x=\frac{3 \pi}{4} \pm \pi n \][/tex]

Therefore, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.